Influência do ângulo de plantio na propagação vegetativa de espécies utilizadas em engenharia natural - Monteiro, Josita Soares (2009)
The vegetation to be employed in techniques proposed by the natural engineering or soil bioengineering needs to fill out some requisites related to ecological, phytossociological and of reproduction aspects. The techniques in natural engineering use the plants in different angles in relation to the land. For this reason, the present work aims to evaluate the effects of different angles of stem cuttings planting of Phyllanthus sellowianus Müll. Arg., Salix humboldtiana Willd. and Sebastiania schottiana (Müll. Arg.) Müll. Arg., in order to determine the most suitable form to the planting of these species. The experiment was conducted in the Laboratory of Silviculture, in the Federal University of Santa Maria (UFSM), Santa Maria, Rio Grande do Sul, in the period of August to November of 2007. The treatments consisted in the three species of stem cuttings planting, in three different angles of planting in relation to the land (10°, 30° and 90°). The stem cuttings with 30 cm of length, with variable diameter from 1.0 to 4.5 cm, were collected in the central region of the state of the Rio Grande do Sul, in the final of August month. Two thirds of the stem cutting s bases were inserted in inert substrate (sand). The experimental design was completely randomized, with 30 repetitions for treatment. After 30 and 60 days, the following parameters were observed: the number of sprouted stem cuttings, number and length of the sprouts, and after 90 days, besides these parameters, were determined the survival, the length, the diameter, and the dry mass of the shoots, and also the length, the diameter, the dry mass and the volume of the roots. The data were statistically analyzed through the statistical programs and Excel. Sebastiania schottiana did not present sprouting, not even rooting, which perhaps could be explained by the stem cuttings time of collection, where that should be tested in other periods of year. The planting angle showed influence on some variables for Phyllanthus sellowianus and Salix humboldtiana. Both the species presented high values of survival, with a tendency for major results for stem cuttings planted in angle of 10° and 90° for Phyllanthus sellowianus (100%) and in angle of 30° for Salix humboldtiana (87%). Significant correlations were observed between the variables of the air part and of the radicial system and the area of transverse section of the stem cuttings, for the different planting angles. Both the two species presented the majority of the roots located on the basis of the stem cuttings, except for the ones planted in angle of 30°, which had the roots distributed along the whole buried portion. The realization of new studies is suggested with other species and also with another angles of planting, as well as the use of bigger diametric breadth.